1993
DOI: 10.1111/j.1439-0434.1993.tb01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Rhizobia in the Control of Root Rot Diseases of Sunflower, Okra, Soybean and Mungbean

Abstract: Biocontrol potential of Rhizobium and Bradyrbizobium against soilborne root infecting fungi was tested. In vitro tests Rhizobium meliloti inhibited growth of Macrophomina phaseolina, Rhizoctonia solani and Fusarium solani while Bradyrhizobium japonicum inhibited M. phaseolina and R. solani producing zones of inhibition. In field R. meliloti, R. leguminosarum and B. japonicum used either as seed dressing or as soil drench reduced infection of M. phaseolina, R. solani and Fusarium spp., in both leguminous (soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(44 citation statements)
references
References 13 publications
(8 reference statements)
3
40
0
1
Order By: Relevance
“…This could be due to their antagonistic effect as reported by Gasoni et al [7], Nelsson [9], Ehteshamul-Shaque and Ghaffar [10], Zheng and Sinclair [11], Lewis and Lumsent [12], Jensen et al [13] and Santamarina and Joseph [14]. These results also were reported by Chen et al [1], Liu et al [30] and Pietrse et al [31] who showed that (PGPR) has been investigate as a possible practical way to use induced resistance to fungal pathogens in various crops.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…This could be due to their antagonistic effect as reported by Gasoni et al [7], Nelsson [9], Ehteshamul-Shaque and Ghaffar [10], Zheng and Sinclair [11], Lewis and Lumsent [12], Jensen et al [13] and Santamarina and Joseph [14]. These results also were reported by Chen et al [1], Liu et al [30] and Pietrse et al [31] who showed that (PGPR) has been investigate as a possible practical way to use induced resistance to fungal pathogens in various crops.…”
Section: Resultsmentioning
confidence: 70%
“…Nelsson [9] reported that Trichoderma spp., are specific biocontrol agents against fungal pathogens (from Pythium to Rhizoctonia) according to the type of antibiotic produced. Under field conditions, Ehteshamul and Ghaffar [10] observed the antagonistic rhizobia and bradirhizobia used as seed dressing or soil drench reduced infection of Rhizoctoia solani in both leguminous and no leguminous plants. Zheng and Sinclair [11] showed that Bacillus megaterium is a potential bacterial biocontrol agent against Rhizoctonia solani.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these results, a mode of action of antifungal activity in culture filtrate is through production of lytic enzymes and antifungal metabolites by B. amyloliquefaciens Y1 in media. Ehtesmul -Haque and Ghaffar (1993) reported that antifungal activity by many antagonistic bacteria is possible through by production of secondary metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Application of rhizobial isolates as seed coating or as soil drench reduced disease incidence of M. phaseolina, R. solani and Fusarium spp. in okra plants [58]. Deshwal et al [42] reported that several rhizobial and bradyrhizobial isolates can effectively suppress the growth of Macrophomina phaseolina causing charcoal rot of ground nut.…”
Section: Discussionmentioning
confidence: 99%